Effects of environmental organochlorine pesticides on human breast cancer: Putative involvement on invasive cell ability. Issue 2 (2nd August 2013) - Pestana, Diogo; Teixeira, Diana; Faria, Ana; Domingues, Valentina; Monteiro, Rosário; Calhau, Conceição
ABSTRACT Human exposure to persistent organic pollutants (POPs) is a certainty, even to long banned pesticides like o, p′‐dichlorodiphenyltrichloroethane (o, p′‐DDT), and its metabolites p, p′‐dichlorodiphenyldichloroethylene (p, p′‐DDE), and p, p′‐dichlorodiphenyldichloroethane (p, p′‐DDD). POPs are known to be particularly toxic and have been associated with endocrine‐disrupting effects in several mammals, including humans even at very low doses. As environmental estrogens, they could play a critical role in carcinogenesis, such as in breast cancer. With the purpose of evaluating their effect on breast cancer biology, o, p′‐DDT, p, p′‐DDE, and p, p′‐DDD (50–1000 nM) were tested on two human breast adenocarcinoma cell lines: MCF‐7 expressing estrogen receptor (ER) α and MDA‐MB‐231 negative for ERα, regarding cell proliferation and viability in addition to their invasive potential. Cell proliferation and viability were not equally affected by these compounds. In MCF‐7 cells, the compounds were able to decrease cell proliferation and viability. On the other hand, no evident response was observed in treated MDA‐MB‐231 cells. Concerning the invasive potential, the less invasive cell line, MCF‐7, had its invasion potential significantly induced, while the more invasive cell line MDA‐MB‐231, had its invasion potential dramatically reduced in the presence of the tested compounds. Altogether, the results showed that these compounds were able to modulate several cancer‐related processes, namely in breast cancer cell lines, and underline the relevance of POP exposure to the risk of cancer development and progression, unraveling distinct pathways of action of these compounds on tumor cell biology. © 2013 Wiley Periodicals, Inc. Environ Toxicol 30: 168–176, 2015.